BEAUTIFUL JUSTICE AND JUST BEAUTY? EXPLORING JUSTICE AND BEAUTY FROM THE PERSPECTIVE OF THE WRONGED - M. Louw (Acta Theologica)
This article will attempt to draw from the deep wells of Nicholas Wolterstorff’s understanding of justice and beauty, respectively, so as to find possible linkages between the two that might be helpful in our quest to understanding this important theme. In order to do this successfully, this article, first, invites readers into Wolterstorff’s understanding of justice based on inherent worth. Hereafter, in a similar fashion, the article explores, as a second theme, Wolterstorff’s understanding of beauty as related to the so-called grand narrative of art. Regarding both themes, I follow a basic structure: outlining the problem; offering critiquing, and exploring possible alternatives. It is hoped that this article will finally, and by way of conclusion, resolve some of this tension between justice and beauty, by examining three specific ways in which Wolterstorff has attempted to link these two themes.